Flying Monsters - BENTON, Michael (Discovering Dinosaurs, 2015)
While dinosaurs roamed the earth, the skied were ruled by pterosaurs. What were these creatures? Which were the biggest? How did they live? Find out the answers to these and other questions about the strange, prehistoric fliers.